Los trabajos intelectuales del anticomunismo: el congreso por la libertad de la cultura en América latina - Marta Ruiz Galbete (Nuevo mundo - Mundos Nuevos, 2013)
Among the organizations that took part in the defence of the Western bloc during the Cold War, the Congress for Cultural Freedom stands out through its large and relevant action. Established in over 35 countries and on all five continents, the CCF set freedom and freedom of creation and research as its raison d’être thus producing a wide range of works and analyses from a pro-American perspective, consistent with the Western values it held as its own. Bearing in mind such a broader picture, this paper will focus on the Latin-American area in order to single out the distinctive features and circumstances which account for the network’s specific action in the subcontinent. Beyond the inevitable mention of the its CIA’s funding we will endeavour to assess the intellectual CCF’s works in Latin America as well as this particular segment of anticommunism it embodied between 1953 and 1973.